Characterization of the integrated gut microbiota and metabolite profiles in osteoporosis patients with different traditional Chinese medicine syndromes - Geng, Zixiang; Yuan, Long; See, Dihang; Zhao, Yongfang (Frontiers in Microbiology, 2025)
IntroductionThis study aims to investigate whether the Traditional Chinese Medicine (TCM) classification of osteoporosis corresponds to specific gut microbial and metabolic profiles, thereby providing a microbiological basis for TCM syndrome differentiation.MethodsBody composition was assessed using dual-energy X-ray absorptiometry in healthy elderly controls and osteoporosis patients categorized by TCM subtype. Gut microbiota composition and metabolite profiles were analyzed via 16S rRNA gene sequencing and liquid chromatography-tandem mass spectrometry (LC-MS/MS), respectively.ResultsThe gut microbiota dysbiosis index was significantly elevated in osteoporosis patients compared to healthy controls, with the highest levels observed in the spleen-kidney Yang deficiency subtype. Distinct microbial signatures were identified: Intestinibacter and Phascolarctobacterium were significantly enriched in kidney Yang deficiency osteoporosis, while Olsenella was markedly increased in spleen-kidney Yang deficiency osteoporosis. Correlation analyses revealed significant associations between these microbial markers and clinical parameters: Intestinibacter and Phascolarctobacterium abundances negatively correlated with bone mineral density at multiple skeletal sites, whereas Olsenella levels were negatively associated with appendicular skeletal muscle index. Importantly, microbial metabolic pathways differed between TCM subtypes, with kidney Yang deficiency associated with vitamin D metabolism and spleen-kidney Yang deficiency linked to lipid metabolism.ConclusionTCM classification captures meaningful biological heterogeneity in osteoporosis, reflected in distinct microbiome and metabolic signatures. These findings provide a microbiological basis for TCM syndrome differentiation and may inform personalized approaches to osteoporosis diagnosis and treatment.